The genus Prothrombosternus (Coleoptera: Curculionidae: Molytinae) rediscovered: a male from Rubeho Mountains, Tanzania - Grebennikov, Vasily V. (Zootaxa, 2016)
A male specimen of the monotypic weevil genus, Prothrombosternus Voss, 1965, so far known on the basis of only five syntypes from Mt. Meru and Mt. Hanang, Tanzania, is reported from the Rubeho Mountains, Tanzania. The lectotype of Prothrombosternus tarsalis Voss, 1965 is designated using a male from Mt. Meru. The Rubeho specimen shares the same external and genital morphological characters with the lectotype (both extensively illustrated) and, therefore, both are considered conspecific. The DNA barcode of the Rubeho specimen is publicly available at dx.doi.org/10.5883/DS-PROTHRO. All six known specimens of Prothrombosternus are flightless and were found by sifting leaf litter at elevations between 1833–2500 m in wet Afromontane forests. The genus is, therefore, thought to be restricted to this highly fragmented habitat threatened by human encroachment. Presence of the genus on both geologically old (Rubeho Mountains; >10Ma) and young (Mt. Meru and Mt. Hanang volcanoes, <2Ma) forested highlands suggests presently unknown means of dispersal. The phylogenetic position of the genus is unknown and its taxonomic placement in Cycloterini cannot be presently tested.